Proceedings of the 49th International Academic Conference, Dubrovnik 2019
DOI: 10.20472/iac.2019.049.035
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure: An Empirical Analysis of Listed Companies in Thailand Stock Exchange Set 100 Index

Abstract: The main purpose of this study is to investigate some financial indicators that affect the debt ratio in Thailand's capital market. Two competing theories that explicate the capital structure are old-fashioned pecking order and static trade-off model. From existing literature reviews, we select seven traditional factors: profitability, asset structure, size, liquidity, non-debt tax shields, dividend policy and growth as explanatory variables. While long-term debt and total debt are used as proxies for dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This result is consistent with Farrukh and Asad (2017), Rao et al (2017), Sanyaolu et al (2018), Deitiana and Komalasari (2017), Naseem et al (2017). However, it contradicts with the research conducted by Khan et al (2018), Imtiaz et al (2016), Hussain et al (2020), Pongsupatt and Pongsupatt (2019), which stated that firm size has an impact on Capital Structure.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…This result is consistent with Farrukh and Asad (2017), Rao et al (2017), Sanyaolu et al (2018), Deitiana and Komalasari (2017), Naseem et al (2017). However, it contradicts with the research conducted by Khan et al (2018), Imtiaz et al (2016), Hussain et al (2020), Pongsupatt and Pongsupatt (2019), which stated that firm size has an impact on Capital Structure.…”
Section: Discussionmentioning
confidence: 57%
“…Some According to Kumar (2017) profitability is mostly defined as the earnings before interest and tax that is scaled by total assets. Findings from Thuraisingam and Kangetharan (2020) research found that profitability is negatively associated with capital structure, which other studies also yielded the results from Farrukh and Asad (2017), Pongsupatt and Pongsupatt (2019), Dalci et al (2019). As profitability increases, this leads to the firm having more internal funds that is used as a source of internal financing.…”
Section: Profitabilitymentioning
confidence: 83%
See 3 more Smart Citations